Multinational Corporation Codes of Conduct: Governance Tools for Corporate Social Responsibility? - Bondy, Krista; Matten, Dirk; Moon, Jeremy (Blackwell Publishing Ltd, 2008)
Research Issue: We investigate the assumption found in code and corporate social responsibility (CSR) literature that suggests codes are primarily associated with the CSR practices of an organization. Research Findings/Results: A web-based study of 150 corporations from three different countries indicates there is little empirical support for this link between codes and CSR. Thus, if a corporation has a code, it is more likely used to govern traditional business concerns, such as compliance with third party governance requirements, internal issues such as conflict of interest, bribery and corruption, insider trading, etc. This is consistent across all three countries. Therefore we must be cautious against assuming a link between codes and CSR. Evidence of the different governance contexts is also briefly discussed. Theoretical Implications: Findings are addressed to theoretical debates about the construction of corporate identity, the amoralization of business, and the globalization of management practices. Practical Implications: Stakeholders must be careful in assuming that the presence of a code indicates CSR commitments or behavior. Stakeholders need to look at the content of the code to confirm or deny this assumption, particularly such stakeholders as investors who tend to use the existence of a code as evidence of CSR practices to tick "check the box."
Keywords: Corporate social responsibility; Corporate governance code; Stakeholders